We Are Best Friends: Animals in Society - Irvine, Leslie (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Friendships between humans and non-human animals were once dismissed as sentimental anthropomorphism. After decades of research on the emotional and cognitive capacities of animals, we now recognize human-animal friendships as true reciprocal relationships. Friendships with animals have many of the same characteristics as friendships between humans. Both parties enjoy the shared presence that friendship entails along with the pleasures that come with knowing another being. Both friends develop ways of communicating apart from, or in addition to, spoken language. Having an animal as a best friend can take the form of relationship known as the "pet", but it can also take other forms. People who work with animals often characterize their non-human partners as friends. People who work with search-and-rescue dogs, herding dogs, or police dogs develop and depend on the closeness of friendship. The same holds for equestrians, as horses and riders must understand each other's bodies and movements intimately. In some situations, animals provide the sole source of affection and interaction in people's lives. Homeless people who live on the streets with animal companions experience togetherness 24/7. This book explores the various forms these friendships take. It sheds light on what these friendships mean and how they expand the interdisciplinary knowledge of the roles of animals in society.